Land Development on high land areas: Comparison of process implementation and legislation effectiveness between Malaysia and Hong Kong - Alias, A.; Ali, A.S.; Othman, K.N. (2014)
The increasing of development failure on highland urges the professionals to develop solution on mitigating the problems. This paper discusses on land development process and legislation on highland development in Malaysia and Hong Kong. This study is focus on land use planning, laws and regulations pertaining to land development process. Hence, this research is to review the current development process including mechanism and legislation pertaining land development on highland in Malaysia and Hong Kong. Hong Kong is chosen as an example based on the fact that for its successfulness in managing highland developments. The main aim of this research is to evaluate the effectiveness of land development legislations and development approaches for highland development. This research reveals the effects and consequences of implementation regulations and development process on highland that have been used at Malaysia and Hong Kong. In Malaysia, land development process on highland is still in questionable; why present property laws and regulations are fail to achieve highland development standards as compared to Hong Kong. There are weaknesses that need to be overcome such as on the implementation and the intensity of the provision in property laws and regulation that can ensure the achievement of required land development process.